Nurse’s role in enhancing adolescents’ perceptions of the dangers of electronic cigarettes. - Jornburom, Yodrawin; Chaiyasung, Phatcharaphan; Yakasem, Panchaporn; Sridet, Rutshaporn; Nanudorn, Anusorn (Thai Journal of Nursing, 2021)
E-cigarettes are illegal products which cause harm to health. However, it has been popular among adolescents, because it contains information for advertising purposes and traded widely in the online media. Because of its easily purchased, the value of new fashion, and information claiming that e-smoking is safer than conventional cigarettes, these provoke teenagers to try on electronic cigarettes. Nurses’ roles in enhancing adolescents’ perceptions of the dangers of electronic cigarettes are as followings: 1) Strengthening coalition partnership for smoke free environment in all areas of hospitals,community, agencies, and workplace; 2) Preventing teenagers for being new smokers who will be further a current smokers; 3) Providing a cessation program for all current smokers; and 4) Promoting smoke-free environment as legally practice on tobacco control, second-hand smoke prevention, and providing knowledge and information of toxicity of tobacco substances. Additional regulations for tobacco control could enhance current smokers’ motivation to quit smoking.